Focal infrared neural stimulation with high-field functional MRI: A rapid way to map mesoscale brain connectomes - Xu, Augix Guohua (Sci Adv, 2019)
We have developed a way to map brain-wide networks using focal pulsed infrared neural stimulation in ultrahigh-field magnetic resonance imaging (MRI). The patterns of connections revealed are similar to those of connections previously mapped with anatomical tract tracing methods. These include connections between cortex and subcortical locations and long-range cortico-cortical connections. Studies of local cortical connections reveal columnar-sized laminar activation, consistent with feed-forward and feedback projection signatures. This method is broadly applicable and can be applied to multiple areas of the brain in different species and across different MRI platforms. Systematic point-by-point application of this method may lead to fundamental advances in our understanding of brain connectomes.